Optimising instructional materials for Covid-19 rapid tests for self-sampling and testing: Mapping the optimization process of manufacturer's instructions for use for self-testing RDTs intended for low-literacy contexts. - Moses Kelly Kumwenda; Madalo Mukoka; Elena Reipold-Ivanova; Owen Mhango; Yasmin Dunkley; Florence Abok; Euphemia Sibanda; Constancia Watadzaushe; Elizabeth L Corbett; Augustine Talumba Choko (PLoS ONE)
Simple and easy to use kits for SARS-Cov-2 self-testing during epidemic waves are needed to optimize diagnostic capacity in low- and middle-income countries. SARS-Cov-2 self-testing kits are available, but application of these novel diagnostic technologies is less understood in low and middle-income contexts. We investigated the ability to understand and perform instructions for use (IFUs) for STANDARD Q COVID-19 Ag Test (SD Biosensor) and Panbio COVID-19 Ag Rapid Test Device (Abbott Rapid Diagnostics) for anterior nares (AN) nasal self-sampling and self-testing for COVID-19 in rural and urban Malawi. Qualitative research methods using iterative cognitive interview approach was used to investigate the ability of healthcare providers and lay community members to understand and perform a COVID-19 self-sample or self-test using the manufacturer's instructions for use. A total of 120 iterative cognitive interviews were done with healthcare providers and lay community members for self-sampling (N = 76) and self-testing (N = 44). Cognitive interviews began with the manufacturers version of instructions for use followed by subsequent iterations to refine problematic instructions. Structured interview guide and an observation checklist were used to collect data which was then coded inductively. A framework analysis approach was used to synthesize qualitative data. Study participants were generally proficient at performing a COVID-19 self-sampling and self-testing using the two COVID-19 Rapid Testing Devices. Several of design and content problems within manufacturer's instructions for use made their contextual application sub-optimal. Overall, participants experienced difficulties because of the omission of essential elements within instructions, use of short texts/phrase or lack of a word instruction, the lack of labels on where to open the package; the inconsistencies between word instructions within the instructions for use and the physical contents of the test package; the inability to digest and apply certain technical concepts and the lack of clarity in the phrasing of some text instructions. As expected, healthcare providers experienced fewer problems compared to lay community members. The refinement of these instructions greatly improved comprehension among lay community members. Self-sampling and self-testing for COVID-19 can be performed lay community members with fidelity in a scaled context if the manufacturer's instructions for use have been refined and tailored to the context. In the current study, we have used the study findings to map the optimisation process of manufacturer's IFU'S for self-testing RDT's intended for low literacy contexts including Malawi.